2011
DOI: 10.1001/archoto.2011.170
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Magnetic Resonance Imaging Characteristics of Acute Invasive Fungal Sinusitis

Abstract: Magnetic resonance imaging is more sensitive for detecting early changes of AFIFS than CT. Both imaging modalities have similar specificities. Perisinus invasion with MRI was the most sensitive and specific single parameter evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
134
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 23 publications
(40 reference statements)
8
134
3
1
Order By: Relevance
“…This finding led to the recommendation that CT be considered a second-line technique. 9 While our study populations were different, our CT-based predictive model nevertheless demonstrated higher sensitivity (95% versus 86%), specificity (86% versus 75%), and NPV (95% versus 60%) than these previously published MR imaging data. 9 Our PPV estimates were similar (87% versus 92%).…”
contrasting
confidence: 46%
See 4 more Smart Citations
“…This finding led to the recommendation that CT be considered a second-line technique. 9 While our study populations were different, our CT-based predictive model nevertheless demonstrated higher sensitivity (95% versus 86%), specificity (86% versus 75%), and NPV (95% versus 60%) than these previously published MR imaging data. 9 Our PPV estimates were similar (87% versus 92%).…”
contrasting
confidence: 46%
“…9 While our study populations were different, our CT-based predictive model nevertheless demonstrated higher sensitivity (95% versus 86%), specificity (86% versus 75%), and NPV (95% versus 60%) than these previously published MR imaging data. 9 Our PPV estimates were similar (87% versus 92%). Moreover, our predictive model even produces higher sensitivity, specificity, and NPV than previously reported with CT. 8,9 The NPV is of particular importance in screening studies because low NPV results in erroneously excluding a patient positive for AIFR.…”
contrasting
confidence: 46%
See 3 more Smart Citations